The Construction of Epistemology of Fatwa on Social Interaction Through Social Media in Indonesia - Karmuji Abu Safar; Teti Hadiati; Athoillah Islamy (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study intends to identify the Islamic legal approach in determining the fatwa of the Indonesian Ulema Council Number 24 of 2017 concerning Law and Social Interaction in Social Media. This literature research is a type of philosophical normative research using an Islamic legal system approach. The results of the study conclude that the determination of the MUI fatwa on laws and guidelines for social interaction through social media uses a holistic approach to Islamic law. This major conclusion can be seen from various characteristics which is: First, the overall character (wholeness) and multidimensionality in the form of the use of universal textual arguments ('aam). Second, the character of purpose in the form of the use of various fiqh rules that emphasize the realization of benefit as the basis as well as the orientation of legal determination. Third, the cognitive character is the use of several classical fiqh ideas, but they are not used as independent arguments, but are combined with various other perspectives that are part of the fatwa arguments. Fourth, the character of openness in the form of an elaboration of the Islamic legal approach with the opinions of experts regarding the use of social media Penelitian ini bermaksud untuk mengidentifikasi pendekatan hukum Islam dalam penetapan fatwa Majelis Ulama Indonesia (MUI) Nomor 24 Tahun 2017 tentang Hukum dan Pedoman Bermuamalah Melalui Media Sosial. Penelitian pustaka ini termasuk jenis penelitian normatif filosofis dengan menggunakan pendekatan sistem hukum Islam. Hasil penelitian menyimpulkan bahwa penetapan fatwa MUI atas pedoman interaksi sosial melalui media social menggunakan pendekatan hukum Islam yang bersifat holistik. Kesimpulan besar inidapat dilihat dari berbagai karakteristik sebagai berikut: Pertama, karakter menyeluruh (wholeness) dan multidimensi dalam penggunaan dalil-dalil nas yang bersifat universal (‘aam). Kedua, karakter kebermaksudan (purpose) berupa penggunaan berbagai kaidah fikih yang menekankan kemaslahatan sebagai dasar penetapanhukum. Ketiga, karakter kognitif berupa penggunaan beberapa pemikiran fikih klasik, namun tidak dijadikan sebagai dalil independen, melainkan dipadu dengan berbagai perspektif lain yang menjadi bagian dalil fatwa. Keempat, karakter keterbukaan dalam elaborasi pendekatan hukum Islam dengan pendapat para ahli terkait penggunaan media sosial.